STUDI PERILAKU INTERAKSI IKAN GUPPY JANTAN DAN BETINA (Poecilia reticulata ) PADA MASA REPRODUKSI - Nugroho, Anwari Adi; Muzaki, Ahmad; Anggraini, Arista Indah; Haryanti, Dwi (Teknosains: Media Informasi Sains dan Teknologi, 2021)
Guppy fish is one type of ornamental fish that has many types. Various body shapes and colors make guppy fish one of the favorite types of ornamental fish to fill the aquarium. The pattern of care and easy breeding makes guppy fish widely cultivated by the community. This study aims to determine the interaction behavior of male and female guppies (Poecilia reticulata) during reproduction. This research was conducted at the practitioner’s house, in December 2020. This research used a descriptive exploratory research which was carried out by observing the behavior of male and female guppies directly based on the behavior patterns that occurred. This study used an ad libtum sampling method. The results showed that male guppies have beautiful bodies and male guppies are actively showing off their body beauty all the time by tilting their bodies upwards while wagging their tails.